Kinematic sequence patterns in the overhead baseball pitch - Scarborough, D. M.; Bassett, A. J.; Mayer, L. W.; Berkson, E. M. (Sports Biomechanics, 2020)
Conceptually, an efficient baseball pitch demonstrates a proximal-to-distal transfer of segmental angular velocity. Such a timing pattern (or kinematic sequence) reduces stress on musculoskeletal structures of the throwing arm and maximises ball velocity. We evaluated the variability of kinematic sequences in 208 baseball pitches. 3D biomechanical pitch analyses were performed on 8-10 fastball pitches from 22 baseball pitchers (5 high school, 11 collegiate and 6 professional). The kinematic sequence patterns - time of peak angular velocity of five body segments: pelvis, trunk, arm, forearm and hand - were measured. None of the pitches analysed demonstrated an entirely proximal-to-distal kinematic sequence. Fourteen different kinematic sequence patterns were demonstrated, with the most prevalent sequence being pelvis -> trunk -> arm -> hand -> forearm. Fewer than 10% of the pitchers performed only one kinematic sequence pattern across the sampled pitches. The variability of the kinematic sequence was similar in high-school pitchers and professionals. Previous studies report that deviation from the proximal-to-distal kinematic sequence is associated with increased injury risk. As a method of evaluating the efficient transfer of energy to the hand, the kinematic sequence may provide insight to injury risk in the future. The ideal kinematic sequence and ideal variability of the sequence when throwing have yet to be determined.